Museum Experience Quality and Word of Mouth Intention: The Critical Role of Emotional Engagement as a Mediator - Triana Rosalina Dewi; Emenina Tarigan; Tri Djoko Sulistiyo; Anita Swantari; Nursyafiqah Binti Ramli (Institut Pariwisata Trisakti, 2026)
This study examines the relationship between museum experience quality, emotional engagement, and word of mouth intention in the context of cultural tourism. A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with data collected from 160 visitors of Museum Wayang in Jakarta through purposive sampling. The results indicate that museum experience quality has a strong and significant effect on emotional engagement. Furthermore, emotional engagement significantly influences word of mouth intention. However, museum experience quality does not have a direct significant effect on word of mouth intention. The indirect effect test reveals that emotional engagement fully mediates the relationship between museum experience quality and word of mouth intention. These findings suggest that high-quality experiences alone are insufficient to stimulate recommendation behavior unless they evoke emotional responses. The study contributes to the tourism literature by highlighting the critical role of emotional engagement as a key mechanism linking experience and behavioral intention, particularly in the context of cultural museums in developing countries. Practically, the findings emphasize the importance of designing immersive and emotionally engaging museum experiences to enhance visitor advocacy. Keywords: museum experience quality, emotional engagement, word of mouth intention